Pengaruh Asimetri Informasi, Manajemen Perpajakan dan Beban Pajak Tangguhan Terhadap Manajemen Laba: (Studi Pada Emiten Sektor Perindustrian BEI Periode 2019-2022) - Avista Yudha, Suchi; Rely, Gilbert; Prayogo, Bambang; Mulyadi; Hasioan Sianipar, Panata Bangar (PT. Alahyan Publisher Sukabumi, 2024)
The study aims to examine the effect of Information Asymmetry, Tax Management, and Deferred Tax Expenses on Earnings Management, the population of industrial sector issuers on the IDX for the period 2020-2022. The research used quantitative data, multiple linear regression, purposive sampling technique, obtained 17 issuers for 4 years, the sample of 68 data, and hypothesis testing using Eviews version 12, the results concluded that (1) Information Asymmetry has a negative and significant effect on Earnings Management, (2) Tax Management has a positive and significant effect on Earnings Management and (3) Deferred Tax Expenses have no significant effect on Earnings Management, (4) Information Asymmetry, Tax Management, and Deferred Tax Expenses simultaneously have a significant effect on Earnings Management.